2013
DOI: 10.4049/jimmunol.1300320
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NF-κB by Opioids in T Cells

Abstract: Opioids potently inhibit a number of physiological and pathophysiological effects such as pain and inflammation in the brain and the periphery. One of the targets of opioids mediating such effects is the proinflammatory transcription factor NF-κB. In neuronal cells, opioids inhibit this factor by inducing I-κB independently on calcium, involving the opioid-mediated activation of the transcription factor AP-1. However, when and how precisely NF-κB is modulated by opioids in T cells are unknown. By using the TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Chronic administration of opioids induces functional interactions between the immune and nervous systems (41)(42)(43)(44). Some factors of the immune system (such as TNF-α, IL-1β, IL-6, and NF-KB) show modifications due to chronic morphine exposure, and these modifications affect hippocampus function (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic administration of opioids induces functional interactions between the immune and nervous systems (41)(42)(43)(44). Some factors of the immune system (such as TNF-α, IL-1β, IL-6, and NF-KB) show modifications due to chronic morphine exposure, and these modifications affect hippocampus function (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, PKCε −/− murine macrophages were found to display an impairment in LPS‐induced IkB‐α degradation and consecutive NF‐kB activation . Furthermore, it has been reported that NF‐kB activity in different cell types is either increased or decreased in response to opioids.…”
mentioning
confidence: 99%
“…Buprenorphine, compared to other opioids, was shown to have the least immune-modulatory effects (Al-Hashimi et al, 2013). In a recent study, Borner and Kraus demonstrated that opioids inhibited NF-κB, a crucial transcription factor in T cell activation, in T cells (Borner and Kraus, 2013). The LCMV-induced meningitis model is strictly dependent on cytotoxic T cells (Kang and McGavern, 2008).…”
Section: Discussionmentioning
confidence: 99%